Árvores de Decisão Desequilibradas para deteção de erros em transações de comércio externo usando técnicas de data mining - Johny Emanuel de Jesus Gueirez (2014)
Nowadays there are frequently large amounts of data, which are used to extract different types of knowledge. A major problem existing in these data are the outliers. The detection of these outliers is important for a variety of applications, such as detecting credit card fraud, network intrusion, fault detection in critical systems, among others. In this project we intend to do a study about the detection of outliers and adopt a way to detect these values through the use of decision tree algorithms.